The Role of Fisherwomen in the Coastal of Wakatobi District - Indriasary, Anita; Hamzah, Nurnaningsih (Jurnal Ilmiah Membangun Desa dan Pertanian, 2020)
Wakatobi District has enormous marine potential, making most of its people work as fishermen. Fishermen in Wakatobi District still have traditional tools and facilities. So that sailing activity still depends on the fishing season and dry season. This limitation of fishing activities affects economic activities, especially coastal women, who are required to be able to help the family economy so that there is a need for the empowerment of coastal women in order to achieve the goals of a coastal community that is socially and economically prosperous. The purpose of this study was to analyze the role of coastal women in improving the family economy in Wakatobi. Collecting data using interviews, questionnaires, and direct observation in the field. This study uses a qualitative descriptive analysis method. The results showed that coastal women can act as wives and housewives as well as play roles as workers, community members, and developing societies. The role of coastal women is referred to as the role of tradition and the role of transition.